Islamizing peoples with Afghani-‘Fundamentalism’? A Critical Review of Bangladeshi Newspaper - Tasnim Tabassum Munmun (Universitas Darussalam Gontor, 2024)
Taliban has re-emerged in the same position of power after 20 years with the withdrawal of US troops by whom the government of Afghanistan was ousted. This study examines how two prominent and highly circulated newspapers in Bangladesh, the Daily Star (DS) and Prothom Alo (PA), respectively English and Bangla dailies, have represented the issue of Taliban’s coming back to power and the withdrawal of US troops from Afghanistan and how they legitimate the Western intrinsic ideology of sense of superiority— for example, accepting authority of the US and invading powers; and vested agenda of the newspapers. It also argues that both newspapers accepted Orientalist perception of Western superiority— for example, encouraging invading parties to stay in Afghanistan and reject the freedom of Afghanistan people, which eventually promote the orientalist ideology at its core agenda— e.g., forming an enemy image of the non-West and perceive Islam and Muslims as a threat. Examining the news and editorials, this study argues that Bangladeshi newspapers have dehumanized and sidelined the people of the occupied land and favored the invaders instead. Therefore, these newspapers were involved in the exclusion process of Afghan people, which once again would mean that Bangladeshi newspapers constructed the image of Other inside us.